2018
DOI: 10.1523/jneurosci.3565-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Inhibition of CGRPα Sensory Neurons Reveals Their Distinct Roles in Neuropathic and Incisional Pain

Abstract: Cutaneous somatosensory neurons convey innocuous and noxious mechanical, thermal, and chemical stimuli from peripheral tissues to the CNS. Among these are nociceptive neurons that express calcitonin gene-related peptide-α (CGRPα). The role of peripheral CGRPα neurons (CANs) in acute and injury-induced pain has been studied using diphtheria toxin ablation, but their functional roles remain controversial. Because ablation permanently deletes a neuronal population, compensatory changes may ensue that mask the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 106 publications
5
46
0
Order By: Relevance
“…Additional studies have reported that treatment with a CGRP antagonist decreases injury-induced mechanical hypersensitivity. (13,14,(28)(29)(30)(31). The ndings of the present study are in accordance with previous observations of improvements as animal with α-CGRP inhibition following optic stimulation showed better improvement in hypersensitivity than animals treated with optical stimulation alone.…”
Section: Discussionsupporting
confidence: 92%
“…Additional studies have reported that treatment with a CGRP antagonist decreases injury-induced mechanical hypersensitivity. (13,14,(28)(29)(30)(31). The ndings of the present study are in accordance with previous observations of improvements as animal with α-CGRP inhibition following optic stimulation showed better improvement in hypersensitivity than animals treated with optical stimulation alone.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, other researchers generated adult mice selectively expressing the outward rectifying proton pump archaerhodopsin in peripheral neurons expressing calcitonin gene-related peptide-α (CANs), and inhibited their peripheral cutaneous terminals in models of SNI with a transdermal light system activation. After SNI surgery, the authors found that brief activation of archeo-rhodopsin on their peripheral cutaneous terminals reversed chronic mechanical, cold, and heat hypersensitivity [136]. In addition, the role of optogenetic stimulations of glia cells has been as well investigated.…”
Section: Cutting-edge Techniques In Sni Model: Focus On Optogenetic Amentioning
confidence: 99%
“…10 Tellingly, optogenetic inhibition of CGRPα-positive neurons transiently and reversibly relieves cold allodynia after spared nerve injury. 58 Ciguatoxins also increase CGRP release and produce flare when injected into humans. 59,60 Using in vivo imaging of the trigeminal ganglion, CGRPα-positive neurons were identified as a mixture of small-diameter polymodal nociceptors that respond to heat and large-diameter mechanonociceptors that respond to noxious mechanical stimulation of the hairy skin.…”
Section: Molecular Identity Of Silent Cold-sensing Neuronsmentioning
confidence: 99%